Efficacy of short-chain polypeptide-based EEN formulas in alleviating intestinal injury in children with Crohn’s disease: a single-center study in China - Wu, Runqiu; Yang, Jin; Cao, Jinjin; Wang, Peng; Wang, Chenhui; Chen, Wenxin; Wu, Yanling; Zheng, Xinguo; Jin, Yu; Yang, Hui (Frontiers in Nutrition, 2023)
Short-chain polypeptides are composed of three to nine amino acids, which can be absorbed by the intestinal tract without digestive enzymes and ATP energy. Crohn’s disease (CD) is a chronic non-specific disease derived from inflammation and damage of the gastrointestinal tract. In this study, we aim to investigate the effect of short-chain polypeptide-based exclusive enteral nutrition (EEN) formulas on intestinal injury in Chinese children with active CD. From January 2013 to January 2019, a total of 84 consecutive children with a diagnosis of Crohn’s disease (CD) in the Department of Pediatric Gastroenterology, Children’s Hospital of Nanjing Medical University, were divided into mild and moderate-to-severe active CD groups. Each group was further divided into two subgroups: drug group and short-chain polypeptide plus drug group. Tests were carried out on the levels of intestinal fatty acid binding protein (I-FABP) in the blood, fecal calprotectin (FC), and occludin protein in the intestinal mucosa 1 day before treatment and 8 weeks after treatment. Endoscopic and histopathological observations were detected to compare the changes in intestinal injury in children with active CD. After 8 weeks of treatment, the SES-CD scores and Chiu scores of the ileocecal area and terminal ileum of children with mild active CD and the ileocecal area of children with moderate-to-severe active CD in short-chain polypeptide plus drug group were significantly lower than those in the drug group. The OD value of occludin in the terminal ileum and ileocecal area of children with mild active CD and the ileocecal area of children with moderate-to-severe active CD after short-chain polypeptide-based EEN formulas and drug treatment was significantly higher than those in the drug group (p < 0.05). Meanwhile, the levels of FC and I-FABP were significantly decreased (p < 0.05). The results showed that short-chain polypeptide-based EEN formulas effectively alleviate intestinal injury in children with active CD.